Analisis Tingkat Penerimaan e-Procurement di Pemerintahan Provinsi Jawa Barat Menggunakan Technology Acceptance Model - Dewi Sri Wahyuni; Aan Julia (Bandung Conference Series: Economics Studies, 2022)
Abstract. This study aims to determine the level of acceptance of technology and Human Resources in the application of e-Procurement in the West Java Provincial Government by using the Technology Acceptance Model with 4 constructs, namely Perceived Easy of Use, Perceived Usefulness, Attitude Toward Using and Behavioral Intention. The government uses technology to reform administration and public services that are transparent and accountable by creating e-Government. The unpreparedness of human resources in operating e-Procurement affects the effectiveness of e-Government. The population in this study is the Regional Apparatus/Bureau in West Java Province, the sample taken is 100 respondents from the Regional Apparatus/Bureau in West Java. The analysis tool uses Partial Least Square SEM (PLS SEM). Researchers used the SmartPLS 3.0 software. The results of the analysis conclude that Human Resources who use e-Procurement in the West Java Provincial Government have accepted the implementation of e-Procurement because e-Procurement provides great benefits in assisting the work of Procurement of Goods and Services although in its application there are still users who have difficulties. Abstrak. Penelitian ini bertujuan untuk mengetahui tingkat penerimaan teknologi dan Sumber Daya Manusia dalam penerapan e-Procurement di Pemerintahan Provinsi Jawa Barat dengan menggunakan Technology Acceptance Model dengan 4 konstruk yaitu Perceived Easy of Use, Perceived Usefulness, Attitude Toward Using dan Behavioral Intention. Pemerintah memanfaatkan teknologi untuk reformasi administrasi dan pelayanan publik yang transparansi dan akuntanbilitas dengan menciptakan e-Government. Ketidaksiapan sumber daya manusia dalam mengoperasikan e-Procurement mempengaruhi keefektifan e-Government. Populasi dalam penelitian ini adalah Perangkat Daerah/Biro di Provinsi Jawa Barat, sampel yang diambil yakni 100 responden dari Perangkat Daerah/Biro di Jawa Barat. Alat analisis menggunakan Partial Least Square SEM (PLS SEM). Peneliti menggunakan software SmartPLS 3.0. Hasil analisis menyimpulkan bahwa Sumber Daya Manusia yang menggunakan e-Procurement di Pemerintahan Provinsi Jawa Barat sudah menerima dalam implementasi e-Procurement karena e-Procurement memberikan manfaat yang besar dalam membantu pekerjaan Pengadaan Barang dan Jasa meskipun dalam penerapannya masih ada pengguna yang memiliki kesulitan.